Recent Progress in Lunar Laser Ranging at Grasse Laser Ranging Station. Issue 3 (7th March 2020) - Chabé, Julien; Courde, Clément; Torre, Jean‐Marie; Bouquillon, Sébastien; Bourgoin, Adrien; Aimar, Mourad; Albanèse, Dominique; Chauvineau, Bertrand; Mariey, Hervé; Martinot‐Lagarde, Grégoire; Maurice, Nicolas; Phung, Duy‐Hà; et al.
Abstract: Based on a fully passive space segment, the lunar laser ranging experiment is the last of the Apollo Lunar Surface Experiments Package to operate. Observations from the Grasse lunar laser ranging station have been made on a daily basis since the first echoes obtained in 1981. In this paper, first, we review the principle and the technical aspects of lunar laser ranging. We then give a brief summary of the progress made at the Grasse laser ranging facility (Observatoire de la Côte d'Azur, Calern Plateau on the French Riviera) since the first echoes. The current performance, driven by the use of an infrared wavelength laser, is presented in the last section for the year 2018. Key Points: The use of an infrared wavelength has improved the capacities of the Grasse lunar laser ranging station in terms of budget link, reflectors numbers, and synodic period observation The lunar laser ranging statistics from the Grasse station over the year 2018 are presented